Mapping Digital Health Technologies for Leprosy in South Asia: A Scoping Review - Arpish Solanki; Abhishek Chaurasia (International Journal of Advanced Health Science and Technology, 2025)
Digital health technologies are increasingly gaining attention as innovative solutions for managing neglected tropical diseases, including leprosy. However, the application of these technologies specifically for leprosy in South Asia remains underexplored. This scoping review aims to systematically map existing literature on digital health interventions targeting leprosy within the region and to categorize these approaches based on their technological frameworks. A comprehensive search was conducted across multiple academic databases, yielding 22 relevant sources, of which 20 were research studies and 2 were public health platforms. The included studies explored a diverse range of digital health tools such as artificial intelligence (AI), mobile health (mHealth), wearable devices, sensors, and public health information systems. These technologies are employed for various critical applications, including early detection of leprosy cases, case management, monitoring nerve damage and ulcers, and enhancing disease surveillance. Notably, AI-based diagnostic models have demonstrated high accuracy, often exceeding 90%, and have been a focal point of research due to their potential to improve early diagnosis and reduce delays in treatment. Mobile health solutions, including teleconsultations, helplines, and SMS-based communication, facilitate patient-provider interactions, especially in remote areas with limited healthcare infrastructure. Wearable sensors and offline data transfer systems are also explored for effective monitoring of nerve damage and ulcer prevention. Despite these advances, the review highlights that other digital intervention areas remain less developed, and the implementation challenges such as infrastructural limitations, connectivity issues, and data interoperability—pose significant barriers, particularly in rural South Asian settings. The review underscores the need for further research to evaluate the long-term effectiveness, scalability, and cost-efficiency of these digital interventions. It also advocates for regional collaboration to bridge gaps in underrepresented countries like Bangladesh, Nepal, and Sri Lanka, ultimately aiming to enhance leprosy control and patient outcomes through technological innovation.